К вопросу о количестве гиалуроновой кислоты и ее фракций в синовиальной жидкости копытных - Куприкова, В.М. (Вестник зоологии, 1971)
Investigations of the content of hyaluronic acid and its fractions in the synovia of shoulder-scapular, ulnar, carpal, knee and tarsal joints of Ungulata Bos taurus L., Equus przewalskii P d., Bos brachiceros Owen , Sus scrofa domestica L., Bison bison L., Cervus (Dama) dama L., Taurotragus oryx L., Cervus elaphus sibiricus S e v. showed that it is not similar not only in homologous joints of different species of animals but also in different joints of one and the same animal. Synovia of carpal and knee joints contains the highest amount of hyaluronic acid. In synovia of the fore-limb joints there is a greater amount of hyaluronic acid than in synovia of the hind limb hemodynamic joints. Concentration of a high-molecular fraction of hyaluronic acid in hyaluronate of normal synovial liquid is much higher than that of low-molecular one. The results of the investigation permits supposing that the biomechanical conditions -and role of different joints of one and the same limb are different.